Targeting and Scaling-up of Agricultural Water Management Interventions in the Black Volta Basin – Ghana: A CPWF V1 MSc Thesis Project - Diabene, Perpetual (CGIAR Challenge Program on Water and Food, 2013)
Majority of the populace in the Upper West Region of Ghana are small-scale farmers who depend mainly on rain-fed agriculture. However, rainfall pattern is uni-modal (April – September) and variable thus making agriculture quite challenging. This has resulted in poverty and food insecurity with migration down south being on the ascendency especially during the dry season. This research therefore seeks to identify the AWM interventions available in the region, assess their biophysical and socio-economic parameters and up-scale the successful ones to other areas that have similar characteristics.